OP0043 Hip fracture in the extreme elderly: The last frontier of a growing public health problem. (23rd January 2014) - Sehgal, A.; Mannalithra, A.; Mithal, A.; Singh, G.; Triadafilopoulos, G.
Abstract : Background: The extreme elderly (≥80 years age, EE) are the most rapidly growing segment of the population in the world, estimated to increase more than 3-fold from 2000 to 2050 1 . There is little epidemiologic data on osteoporotic hip fractures in EE even though they will represent more than 25% of US population by 2050 2 . Objectives: To study the number and prevalence of hospitalizations for osteoporotic hip fractures in the elderly (65-79 years, E) and extreme elderly (≥80 years, EE) in the US over 16 years (1993-2008). Methods: The Nationwide Inpatient Sample (NIS) is a stratified random sample of all US community hospitals, with detailed information on all hospitalizations, regardless of payer. We examined hospitalizations in NIS from 1993 to 2008 with diagnoses of non-traumatic (osteoporotic) hip fractures in E and EE cohorts. Patients were excluded if there was major trauma, open fractures, or femoral tumors. All prevalence rates were expressed per 100, 000 US population. Results: We studied 4.3 million osteoporotic hip fracture hospitalizations in 565.4 million person-years of observation in individuals ≥65 years from 1993 to 2008. Of these, 67.3% occurred in the EE. Hip fracture hospitalizations in E decreased from 96, 928 in 1993 (386 per 1, 000 person-years) to 80, 987 in 2008 (294 per 1, 000 person-years) (p<0.001), even as the number of these individuals increased from 25.1 million in 1993 to 27.1 million in 2008, perhaps reflecting increasing awareness, screening and treatment for osteoporosis. However, in the EE group, osteoporotic hip fracture hospitalizations increased from 172, 209 in 1993 to 180, 428 in 2008, even as the hip fracture prevalence decreased from 2, 236 per 1, 000 person-years in 1993 to 1, 600 per 1, 000 person-years in 2008 (p<0.001). The increase in the absolute number of hip fracture hospitalizations, in spite of decreasing prevalence, is coincident with the dramatic rise in the number of the EE population, from 7.7 million in 1993 to more than 11.2 million in 2008 (46% increase). While the EE comprised 41.3% of the elderly population in 2008, they accounted for over 69% of all osteoporotic hip fracture hospitalizations, up from 64% in 1993 (p<0.05) (Table). Conclusions: Osteoporotic hip fractures pose a growing problem in the EE, more so than older adults, increasing their risk for hospitalization, morbidity and mortality greatly. The projected exponential growth in EE population threatens a potential epidemic status for osteoporotic hip fractures. This calls for more aggressive measures towards recognition, prevention and therapy of osteoporosis during the medical care of EE, both ambulatory and in assisted living facilities, where preventive care is not routinely considered or provided. References: Perls, T. Health and disease in people over 85. BMJ 2009; 339: b 4715 Soldo BJ, Agree EM. America's elderly. Popul Bull. 1988 Sep;43(3):1-53. Disclosure of Interest: None Declared